Global Research Trends on Herbal Medicine for Hypertension: A Bibliometric and Visual Analysis from 1979 to 2025 - Moch Saiful Bachri,; Danang Prasetyaning Amukti,; Daru Estiningsih,; Kaffah, Silmi; Pratami, Ria Indah (Scripta Medica, 2026)
Hypertension is a major risk factor for cardiovascular disease globally. Despite widespread availability of conventional treatments, blood pressure control rates remain low globally. Herbal medicine is an alternative or complementary medicine that is gaining increasing attention. Scientific analysis is needed to understand the dynamics of global research on this topic. This study uses a data-driven bibliometric approach from Scopus, covering publications from 1979 to 2025. The analysis was conducted using Biblioshiny and VOSviewer software to evaluate publications, collaborations and keyword trends. A total of 2,954 documents were analysed with an annual growth rate of publications of 9.74 % and an average of 31.38 citations per document. China, the United States and India were the countries with the highest contributions in terms of both publications and citations. Institutions such as the China Academy of Chinese Medical Sciences and China Medical University emerged as the most active research centres. Plants such as Allium sativum, Hibiscus sabdariffa and Olea europaea were the main focus of research. Keyword clusters indicated two major focuses: clinical and pharmacological aspects. International collaboration was still relatively low (17.81 %) but showed potential for growth. Research on herbal medicine for hypertension shows steady growth and multidisciplinary approaches.